Ethical issues in clinical trials - Marmont, Alberto (Medicina e Morale, 2024)
Clinical experimentation in all its aspects is an obligatory part of the ideal scope of the subject matter dealt with at the conference in Genoa. Of the two fundamental directives, one on clinical pharmacology and the other on the ethics that governs its execution, it is clear that the latter will be given maximum development here; while noting that there is no dualism between the applied discipline and the theoretical-moral approach, but rather that tout se tient, from the chemical-pharmacological discovery of the new remedy to the decision to use it in man and the clinical practice of application.